2016
DOI: 10.1177/0271678x15615133
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis-related white matter microstructural change alters the BOLD hemodynamic response

Abstract: Multiple sclerosis (MS) results in inflammatory damage to white matter microstructure. Prior research using bloodoxygen-level dependent (BOLD) imaging indicates MS-related alterations to brain function. What is currently unknown is the extent to which white matter microstructural damage influences BOLD signal in MS. Here we assessed changes in parameters of the BOLD hemodynamic response function (HRF) in patients with relapsing-remitting MS compared to healthy controls. We also used diffusion tensor imaging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 85 publications
(153 reference statements)
2
19
0
Order By: Relevance
“…Thus, most fMRI studies utilize a canonical HRF in analysis (see Lindquist et al, 2009). However, it is known to vary considerably in aging and disease (e.g., Bonakdarpour, Parrish, & Thompson, 2007;D'Esposito et al, 1999;D'Esposito, Deouell, & Gazzaley, 2003;Hubbard et al, 2016a;Rypma & D'Esposito, 2001;Zou et al, 2011). Because of the reliance upon neural-vascular communication to produce this canonical shape (e.g., Buxton et al, 2004;Martin et al, 2006), comparisons between healthy individuals and those with known neural-vascular coupling compromise would permit testing of hypotheses regarding the importance of an intact neural-vascular coupling system to optimal neural and cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, most fMRI studies utilize a canonical HRF in analysis (see Lindquist et al, 2009). However, it is known to vary considerably in aging and disease (e.g., Bonakdarpour, Parrish, & Thompson, 2007;D'Esposito et al, 1999;D'Esposito, Deouell, & Gazzaley, 2003;Hubbard et al, 2016a;Rypma & D'Esposito, 2001;Zou et al, 2011). Because of the reliance upon neural-vascular communication to produce this canonical shape (e.g., Buxton et al, 2004;Martin et al, 2006), comparisons between healthy individuals and those with known neural-vascular coupling compromise would permit testing of hypotheses regarding the importance of an intact neural-vascular coupling system to optimal neural and cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Greater variation in underlying hemodynamic systems seen in groups such as older adults (Hutchison et al, 2013a,b;Tsvetanov et al, 2015) and MS patients (DeLuca et al, 2008;Pantano et al, 2005;Rocca et al, 2002;Wegner et al, 2008;cf. Genova et al, 2009;Hubbard et al, 2016a;Lee et al, 2000;White et al, 2009) challenges the assumptions necessary for use of canonical HRFs in group comparison studies. In this way, HRFs derived from the use of a canonical function could be biased in their characterization of the BOLD signal response (cf.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MS patients show relationships between their BOLD functional responses and white matter diffusion characteristics, demonstrating a link between grey matter function and WMMS in this group [Hubbard et al, a; see also Alshowaeir et al, ; Au Duong et al, ]. Although the two are related, it is important to emphasize a distinction between white matter macrostructural (i.e., lesions) and microstructural (i.e., WMMS) alterations in MS because (1) MSā€related alterations to WMMS exist outside of apparent lesioned tissue [e.g., De Keyser et al, ; Klistorner et al, ; Sorbara et al, ] and (2) measures of WMMS account for variance in measures of MS patients' neural function separate from the degree of patients' macrostructural damage [e.g., Hannoun et al, ; Hubbard et al, ]. In one study, for instance, we found that grey matter BOLD response amplitudes were strongly related to individual differences in MS patients' white matter diffusion characteristics, however, no such relationship was found between grey matter BOLD and the extent of white matter macrostructural damage [i.e., lesion burden; Hubbard et al, a].…”
Section: Introductionmentioning
confidence: 99%